THE FINAL OUTCOME IN THE TREATMENT OF LEGG-CALVE-PERTHES DISEASE USING THE COMBINATION OF ILIZAROV METHOD OF TREATMENT AND TUNELISATION (CASE REPORT) - Krivokapić, Branislav; Bukva, Bojan; Jeremić, Danilo; Bogosavljević, Nikola; Tomić, Slavko (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Legg-Calve-Perthes disease (LCPD) is a common childhood hip disease, affecting approximately 0.8 in 100,000 children. It usually affects children between 4 and 8 years old, and boys are more affected than girls. One hip is initially affected, but bilateral localization is present in 9-15 of the cases. The primary treatment in LCPD focuses on containing the femoral head in the acetabulum, thus preventing mollification and fragmentation. The most common surgical treatment method consists of either femoral or pelvic osteotomy or a combination of both. This paper aims to present a minimally invasive alternative method for treating LCPD. Case report: We are presenting a case report of a 19-year-old with a lengthy history of illness. His treatment started at the age of 5, and this is an update on his condition 14 years after the surgery. Conclusion: Hip arthrodiastasis using the Ilizarov circular frame combined with femoral head and neck tunneling is a minimally invasive surgical procedure. From a technical standpoint, this is a relatively demanding procedure that results in shorter in-patient treatment, reduced risk of complications, and cost compared to pelvic and femoral osteotomy.